2016
DOI: 10.1172/jci.insight.89790
|View full text |Cite
|
Sign up to set email alerts
|

Oral ruxolitinib induces hair regrowth in patients with moderate-to-severe alopecia areata

Abstract: IntroductionAlopecia areata (AA) is a major medical problem and is among the most prevalent autoimmune disease in the US, with a lifetime risk of 1.7% (1). AA affects both sexes across all ethnicities and represents the second most common form of human hair loss, second only to androgenetic alopecia (2). AA usually presents with patchy hair loss. One-third of these patients will experience spontaneous remissions within the first year. However, many patients' disease will progress to alopecia totalis (AT, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
202
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 243 publications
(227 citation statements)
references
References 26 publications
2
202
0
6
Order By: Relevance
“…Several studies have shown its effectiveness in the treatment of AA, and it was also found to be beneficial for the more severe types, AT and AU [17,18,19]. The current report further highlights the effectiveness of the JAK inhibitors to treat AA, also in recalcitrant and chronic cases.…”
Section: Discussionsupporting
confidence: 64%
“…Several studies have shown its effectiveness in the treatment of AA, and it was also found to be beneficial for the more severe types, AT and AU [17,18,19]. The current report further highlights the effectiveness of the JAK inhibitors to treat AA, also in recalcitrant and chronic cases.…”
Section: Discussionsupporting
confidence: 64%
“…Several case series and individual reports have documented regrowth of hair in patients with different forms of alopecia areata, including alopecia universalis, following treatment with oral JAK inhibitor drugs. Three JAK inhibitors have been used: tofacitinib 194198 , ruxolitinib 2,199,200 , and baricitinib (JAK 1/2 inhibitor) 201 . Hair regrowth has also been observed when treating human patients with JAK inhibitors for other diseases who have concurrent alopecia areata.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of reports is small, and no randomized, placebo-controlled studies have yet been performed, the response in patients with severe alopecia (in which spontaneous remission is rare) strongly suggests a therapeutic effect. Not surprisingly, there have been several reports of relapse following initial improvement in patients treated with ruxolitinib and tofacitinib 196,197,200,202 , suggesting that an eventual therapeutic regimen may need to include long-term maintenance therapy. The overall positive results in these early clinical studies are supported by the results of JAK inhibition in a mouse model of alopecia areata and by an improved understanding of the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…ruxolitinib-treated patients (5) and in Mackay-Wiggan et al (16), adequately predicted patient response to ruxolitinib, and it was not able to stratify SRs from NRs to tofacitinib. This is not surprising, as the target specificity of the drugs differs and because there was a predominance of AT and AU patients in this study, rather than patch-stage AA in the ruxolitinib trial, or, alternatively, because our study analyzed patients at 2 months after treatment with tofacitinib, which may not represent a complete response or reversion of gene expression signatures.…”
Section: I N I C a L M E D I C I N Ementioning
confidence: 99%